Peran Rumah Qur’an Fakfak Dalam Meningkatkan Minat Baca Al-Qu’an Dan Pembentukan Akhlakul Karimah Anak - Siti Nur Wasis; Ahmad Dimyati Badruzzaman; Ubaidillah Al-Ghifary (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Qur'an is the holy book owned by Muslims and accepted by the last prophet, Prophet Muhammad SAW and also as the last book to perfect the previous books. The Al-Qur'an must be read correctly according to the makhraj, the nature of the letters, understood and practiced in daily life so that people can practice the Al-Qur'an both textually, verbally and culturally. In the Al-Qur'an and Hadith it has been stated that the Islamic religion encourages its followers to develop intelligence, starting with learning to read and write and then by learning various kinds of knowledge. The fact that the majority of people in Indonesia who are Muslim are aware that their ability to read the Koran is very minimal, this is a matter of concern and requires special focus to address it. This phenomenon has led to the emergence of many educational institutions with the vision of developing non-formal education in the field of tahsin and tahfizh (memorization), as well as internalizing the values of the Koran and forming Islamic morals and personality. The role of the Fakfak Qur'an House in the formation of children's morals in the Pariwari District, Fakfak Regency, West Papua, through two processes, namely education in the classroom and a practical process. The activities carried out by Fakfak Qur'an House (FQH) are activities with the aim of increasing children's interest in reading the Al-Qur'an.